E-selectin as a prognostic factor of patients hospitalized due to acute inflammatory respiratory diseases: a single institutional study - Nakano, Hiroshi (EXCLI J, 2019)
When examining patients with acute inflammatory respiratory diseases, it is difficult to distinguish between infectious pneumonia and interstitial pneumonia and predict patient prognosis at the beginning of treatment. In this study, we assessed whether endothelial selectin (E-selectin) predicts the outcome of patients with acute inflammatory respiratory diseases. We measured E-selectin serum levels in 101 patients who were admitted to our respiratory care unit between January 2013 and December 2013 because of acute inflammatory respiratory diseases that were eventually diagnosed as interstitial pneumonia (n = 38) and lower respiratory tract infection (n = 63). Seven of these patients (n = 101) died. The pneumonia severity score was significantly higher and the oxygen saturation of arterial blood measured by pulse oximeter (SpO(2))/fraction of inspiratory oxygen (FiO(2)) was significantly lower in the deceased patients than in the surviving patients. There were significantly fewer peripheral lymphocytes and significantly higher E-selectin serum levels in the deceased patients than in the surviving patients. In the multiple logistic regression analysis, the E-selectin serum levels and SpO(2)/FiO(2) ratio were independent predictive factors of prognosis. The risk of death during acute respiratory disease was determined using a receiver operating characteristic (ROC) curve analysis. The area under the curve (AUC) was 0.871 as calculated from the ES, and the cutoff value was 6453.04 pg/ml, with a sensitivity of 1.00 and a specificity of 0.72 (p = 0.0027). E-selectin may be a useful biomarker for predicting the prognosis of patients with acute inflammatory respiratory diseases.